Radical left party family in Western Europe 1989 -2015 - Chiocchetti, Paolo 1982- (Routledge studies in radical history and politics, 2017)
Toward an analysis of the contemporary Western European radical left -- The Western European landscape, 1914-1988 -- The Western European landscape, 1989-2015 -- The German radical left : a success story -- The Italian radical left : the story of a failure -- The French radical left : success or failure? -- Filling the vacuum? : The trajectory of the contemporary radical left in Western Europe